Analisis Social Media Pada UMKM Ditinjau Dari Perspektif Open Innovation Dan Human Capital - Prima Yulianti; Ratni Prima Lita; Verinita Verinita; Rida Rahim (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
The use of social media and understanding in the field of Information Systems (IS) in the early stages of business activities is a new phenomenon. Social media can provide additional customer and industry data to digitally transform information into knowledge for innovation. Such an amalgamation provides a potentially complementary role in the relationship between human capital and innovation outcomes. Through social media technology, small and medium enterprises (MSMEs) can communicate information and respond to competitors with minimal costs. The ability to share and access information can affect the performance of MSMEs. One important aspect that has emerged recently is open innovation. A previous study has highlighted the importance of human capital for innovation performance. The purpose of this study is to conceptualize the use of social media in an effort to improve the performance of MSMEs from an open innovation-based human capital perspective. The method used is a literature review that is relevant from 2018 to 2022. The results show that the importance of using social media and human capital has a synergistic relationship that has a direct effect on open innovation in improving MSME performance.